2013
DOI: 10.1002/hlca.201200331
|View full text |Cite
|
Sign up to set email alerts
|

New Triterpenes from Gymnema sylvestre

Abstract: Phytochemical investigation of the aerial parts of Gymnema sylvestre has led to the isolation of seven new triterpenes, six oleane types (5, 7–11) and a new lupane type (12), and of the six known analogues 1–4, 6, and 13. The structures and relative configurations of these compounds were elucidated by spectroscopic analyses, including 1D‐ and 2D‐NMR spectroscopy and mass spectrometry, and by the comparison of their NMR data with those of related compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The CH 2 Cl 2 extract showed the highest DPPH· and OH scavenging activities and from its investigation we have isolated thirteen triterpenes (1-13, Figure 1) [15]. …”
Section: Resultsmentioning
confidence: 99%
“…The CH 2 Cl 2 extract showed the highest DPPH· and OH scavenging activities and from its investigation we have isolated thirteen triterpenes (1-13, Figure 1) [15]. …”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, this plant has been and is still being studied by many research groups, as demonstrated by the publication of thousands of articles and the isolation of one hundred new and known molecules. However, few of the oleane triterpenoids isolated from GS that are gem-dimethylated at C-4 (see Figure 1 and Table 3 and Table 4 [80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95], Table 5 [89,95,96,97,98,99,100,101,102,103,104,105], Table 6 [81,82,83,88,89,91,92,93,94,95,103], Table 7 [51,89,95,99,100,104,105,106,107,108,109]) have been assayed (see Figure 1 and Table 8 [81,82,88,89,...…”
Section: Discussion Of the Specific Biological Activity Of Tested mentioning
confidence: 99%
“…The chemical components of G. sylvestre have been confirmed the presence of pregnane glycosides, [1] gymnemic acid glycosides, [2] and oleanane saponins. [3,4] Herein, we reported the isolation and structural elucidation of three pregane-type triterpene glycosides from the leaves of G. sylvestre (figure 1).…”
Section: Introductionmentioning
confidence: 99%